Bio-inspired hybrid nanoparticles promote vascularized bone regeneration in a morphology-dependent manner. Issue 18 (17th March 2017) - Yang, Gaojie; Liu, Haoming; Hu, Xixi; Chen, Zetao; Friis, Thor E.; Wang, Jianglin; Xiao, Yin; Zhang, Shengmin
Abstract : Nanoparticle-embedded scaffolds are used for bone repair: by providing scaffolds with different nano-topologies, the nanoparticles mediate in vivo bone regeneration in a morphology-dependent manner. Abstract : Current major obstacles for translating the nanoparticle (NP) morphology-related function into therapeutic purposes come from the challenges in understanding the mechanisms that determine cell lineage commitment and constructing a NP-based 3D functional structure, and few studies have successfully demonstrated clear evidence of regulating in vivo tissue regeneration by NP morphology so far. Here, we show that nanoparticle geometry can be harnessed to mediate bone regeneration in a rat cranial defect model. We successfully synthesized hydroxyapatite NPs with well-defined morphologies using a modified liquid–solution–solid (LSS) method. The NPs showed differential effects on stem cell behaviors such as particle uptake, autophagy activation and osteogenic differentiation. By integrating nanoparticles within gelatin, we achieved 3D scaffolds with uniformly-distributed nano-topologies which, can mediate in vivo osteogenesis through stimulation of autophagy, with spherical particles demonstrating the most robust bone formation capacity compared to other NPs. Our current work proposes a morphology-dependent effect of NPs on vascularization and bone formation and provides an innovative and feasible strategy for bone regenerative therapies.